Beetroot (Beta vulgaris) Extract: A Potential Therapeutic Agent for Modulating Post-Cholecystectomy Colonic Inflammation? An In Vivo Evidence Review - Mahmudin Ardian Ashadi; Sigit Adi Prasetyo; Yora Nintida (HM Publisher, 2025)
Background: Cholecystectomy, while a common and effective treatment for symptomatic gallstones, can induce alterations in bile flow and gut microbiota composition, potentially leading to colonic inflammation. Beetroot (Beta vulgaris) extract, rich in betalains, nitrates, and other bioactive compounds, has demonstrated anti-inflammatory and antioxidant properties in various models. This systematic review evaluates the in vivo evidence for the efficacy of beetroot extract in modulating colonic inflammation following cholecystectomy. Methods: A systematic search of PubMed, Scopus, Web of Science, and Embase databases was conducted from January 2013 to May 2024, using keywords related to